Pengaruh Karakteristik Peternak Terhadap Pendapatan Usaha Ternak Sapi Madura di Kecamatan Waru Kabupaten Pamekasan - Samsukdin, Samsukdin; Tamami, Novi DB; Hasan, Fuad (Universitas Sebelas Maret, 2023)
Waru Barat Village is a Madura cattle center located in Waru District, Pamekasan Regency. Many people have Madura cattle farming businesses, but the situation on the ground shows that Madura cattle farms are still not supported. This study aims to analyze the characteristics of farmers and the amount of income of farmers, analyze the effect of breeder characteristics on income, and analyze the feasibility level of the Madura cattle business. Sampling using purposive sampling method with a sample size of 43 respondents. The analytical method used is descriptive quantitative with multiple linear regression and R/C ratio. The results of this study are that farmers in Waru District are classified as productive age, low education level, the number of livestock ownership is two tails with around 26 years of experience and has a family of two people and a small proportion are members of farmer groups. The average income earned by farmers is Rp1,166,390 per year. The characteristic factor that has a significant effect on the income of the Madura cattle business is the number of livestock ownership. The R/C ratio is 1.04, which means that the Madura cattle business is profitable, so it can be cultivated. Efforts that can be made to increase the income of farmers are developing the Madura cattle business by increasing the number of livestock ownership through the empowerment of communal cages to reduce farming costs incurred by farmers.